Lexical Errors in Academic Writing at Muhammadiyah University of Tangerang Students’ : Lexical Errors in Academic Writing at Muhammadiyah University of Tangerang Students’ - Putra, Aidil Syah; Cahyani, Yunita Lintang; Azahra, Dimah (Indonesian Journal Publisher, 2024)
Language writing errors are something that often happens. Especially for language learners. In Indonesia, English is a foreign language. This makes language learning feel a little difficult in writing. Lexical errors are mistakes related to the vocabulary of a language. These errors can be broadly defined as deviations from the standard usage of words, which result in incorrect or unclear expressions. This research is an analysis of 6th semester English language education students at Muhammadiyah University, Tangerang. The student writing that is studied is the result of the writing contained in the foreword section of the student's paper assignment. There were 15 students who were used as a sample for analysis this time. The results show that there are four out of seven types of lexical errors in students' writing. These are errors in choosing words (60%), collocation errors (13%), redundancy errors (20%), and spelling errors (7%).